2013
DOI: 10.1017/s001447971300015x
|View full text |Cite
|
Sign up to set email alerts
|

Modelling Yields of Non-Irrigated Winter Wheat in a Semi-Arid Mediterranean Environment Based on Drought Variability

Abstract: Regression models for the prediction of grain yields of non-irrigated winter wheat in a semi-arid Mediterranean environment were developed based on drought variability. Twenty-five years (1980-2004) of climate data and yield data from four soils (sandy loam, clay, clay loam and sandy clay loam soil) in northern Greece were used for this purpose. Two variables were selected as explanatory variables of the models: (a) the monthly precipitation versus the monthly reference evapotranspiration ratio (P/ETo ), which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…The modelling of future scenarios emphasises that areas characterised by drier conditions are more vulnerable to further reductions in precipitation (amplified or modulated by possible shifts in potential evapotranspiration) that will cause a decline in the moisture content of soils available for plants (Nastos et al 2013). Field research and modelling have demonstrated the effects of reduced amounts of precipitation, including water stress and drought on modern yields of rain-fed winter wheat and barley in Greece (Halstead 1989: 72-73;Kosmas et al 1993;Aschonitis et al 2013;Tigkas & Tsakiris 2015). Starting from a lower baseline value for precipitation, the impact of drier conditions would have been stronger in the already drier north-east, where reduced precipitation levels could affect agricultural output directly.…”
Section: Precipitation Variability In the Peloponnesementioning
confidence: 99%
See 1 more Smart Citation
“…The modelling of future scenarios emphasises that areas characterised by drier conditions are more vulnerable to further reductions in precipitation (amplified or modulated by possible shifts in potential evapotranspiration) that will cause a decline in the moisture content of soils available for plants (Nastos et al 2013). Field research and modelling have demonstrated the effects of reduced amounts of precipitation, including water stress and drought on modern yields of rain-fed winter wheat and barley in Greece (Halstead 1989: 72-73;Kosmas et al 1993;Aschonitis et al 2013;Tigkas & Tsakiris 2015). Starting from a lower baseline value for precipitation, the impact of drier conditions would have been stronger in the already drier north-east, where reduced precipitation levels could affect agricultural output directly.…”
Section: Precipitation Variability In the Peloponnesementioning
confidence: 99%
“…1993; Aschonitis et al . 2013; Tigkas & Tsakiris 2015). Starting from a lower baseline value for precipitation, the impact of drier conditions would have been stronger in the already drier north-east, where reduced precipitation levels could affect agricultural output directly.…”
Section: Precipitation Variability In the Peloponnesementioning
confidence: 99%
“…125 Foxhall andForbes 1982;Isager and Skydsgaard 1992, 20-6;Braun 1995. 126 Liakatas 1997Dalezios et al 2002;Mavromatis 2007, 915;Reidsma et al 2009, 32;Aschonitis et al 2013;Tigkas and Tsakiris 2015, 98. 127 Tyrt.…”
Section: Agriculture and The Grain Trade In The Achaian Leaguementioning
confidence: 99%
“…According to Aschonitis et al [53], the mean value of long-term yield of winter wheat in different soils of the Thessaloniki region is strongly associated with clay percentage. The yields showed a bell-shaped response versus the increase of clay, where values below <20% and values >50% were responsible for an~25% yield decrease in comparison to the maximum observed mean yields (see Figure 2 in [53]).…”
Section: Soil Texture and Organic Mattermentioning
confidence: 99%
“…According to Aschonitis et al [53], the mean value of long-term yield of winter wheat in different soils of the Thessaloniki region is strongly associated with clay percentage. The yields showed a bell-shaped response versus the increase of clay, where values below <20% and values >50% were responsible for an~25% yield decrease in comparison to the maximum observed mean yields (see Figure 2 in [53]). The yield decrease for low clay values is probably connected to a lower cation exchange capacity (a low degree of nutrient retention) and a lower water holding capacity and availability, while the respective decrease for the high clay values is probably associated with low soil aeration, problems in water movement, and low water availability due to the higher degree of moisture retention at lower water potentials, which make it difficult for plants to uptake water.…”
Section: Soil Texture and Organic Mattermentioning
confidence: 99%